Closer and Closer Apart Jealousy in Literature - Lloyd, Rosemary (Cornell University Press, 2019)
Envy, Rosemary Lloyd says, involves what one would like to have but does not; jealousy, what one has but fears losing. Lloyd demonstrates in Closer and Closer Apart how the passion unleashed by jealousy can illuminate such concepts as self and other, gender and society. Jealousy, in her view, exerts a powerful attraction in literature, partly because it distorts the individual's perceptions of the other in highly productive ways, and partly because it serves as paradigms for reading and for storytelling.In this accessible and elegantly crafted book, Lloyd explores sexual jealousy more as a literary devise than as a literary theme. She draws her examples from novels, plays, and poetry spanning many years and from many countries, mainly nineteenth- and twentieth-century France and England but also Russia, Poland, Germany, Italy, the United States, Canada, and Australia. Among the writers she treats are Proust, Tolstoy, Dostoyevsky, Charlotte Brontë, Trollope, Barthes, and Baudelaire.After discussing various portraits of the jealous lover, Lloyd asks to what extent the literary experience of jealousy has been colored by conventional images of male and female roles. She also examines the ways in which the jealous lover deals with the "other"-whether beloved or rival. Finally, she looks at jealousy as a desire for control, represented through images of incorporation and possession